Diversity and habitat preferences of bdelloid rotifers in mosses and liverworts from beach forest along sand dunes in Thailand - Sittikron Jattupan; Rapeepan Jaturapruek; Phannee Sa-ardrit; Janejaree Inuthai; Chatchai Ngernsaengsaruay; Supiyanit Maiphae (PeerJ)
Microscopic animals are often thought to be widely distributed due to their small size and specific adaptations. However, evidences show that bdelloid rotifers in bryophytes exhibit habitat specialization, with species composition varying by microhabitat. This indicates that their distribution is influenced by complex ecological processes, warranting further research, particularly at the microscale. In this study, we tested whether species richness and composition of bdelloid rotifers differ across bryophyte species, forms, characteristics, and seasons to understand their ecological distribution and habitat preferences in limnoterrestrial environments. Bdelloid rotifers were identified and counted from bryophyte samples collected in April (low rainfall), August (moderate rainfall), and December 2022 (high rainfall) at Bang Burd Beach Forest, Chumphon Province, Thailand. The results revealed high bdelloid diversity, with 22 species identified, 14 of which are new records for Thailand, raising the known number to 30. However, species richness did not vary across bryophyte variables or seasons, with substantial overlap in species composition across these variables. Additionally, there was no strong habitat preference between bdelloid rotifers and bryophyte species. These results confirm a low degree of habitat specialization of bdelloid rotifers in tropical limnoterrestrial environments.